Turismo, realidade virtual experiência turística: aproximações reflexivas - Taufer, Lisele (My University, 2021)
Tourism, a multifaceted phenomenon, is also an activity that develops itself according to the world revolutions, and one of the characteristics that constitutes it is the mnemic / affective experience, which marks the subject / tourist?s life. The revolutions, the technological ones for instance, create new ways of doing and thinking about tourism. The aim of this study is to characterize and analyze the immersive experience of Virtual Reality provided by the use of the Headset device, in its relationship with tourism. For such an achievement, it is considered: the postmodernism has set new ways for the subjects to interact; technologies are an intrinsic part of these new configurations and organizations, including temporal and spatial ones; the subjects are always on the move (from different nature); virtual reality is characteristic of the postmodernism; the coexistence of different tourism conceptual approaches and the subjectivities existent in tourist experiences. The methodology used is qualitative, and, as a type of research, it seeks to understand the research problem from the available theories, analyzing them and establishing connections to explain the immersive tourist experience that occurs in the virtual space. Therefore, aspects that characterize the mostly bibliographic research nature. To form the theoretical framework, conceptual approaches were built about tourism, travel, movement, tourist experience, immersive experience, territory, virtualization and cyberculture then it is possible to think and answer the question: the experience resulting from the immersion provided by the use of headsets and an interactive multisensory Virtual Reality platform, with 360° visual content, can it be considered tourist? Thus, if tourism is characterized as physical displacement, it is not possible to assume the existence of a virtual tourism experience; however, if the theoretical-analytical basis changes, considering tourism as a movement into the unknown, the possibility that an experience with 3D glasses can also be characterized as tourist must be considered. In the process, many other questions are still unanswered, but the answer to the initial question, whether the experience performed with 3D glasses is considered tourist or not, will depend on the analytical lenses on which the phenomenon is being investigated. There is already a positive signal in the literature for this questioning [resumo fornecido pelo autor].
O Turismo, fenômeno multifacetado, é, também, uma atividade que se desenvolve consoante às revoluções mundiais, e uma das características que o constitui é a experiência mnêmica/afetiva, que marca a vida do sujeito/turista. As revoluções, entre elas as tecnológicas, imprimem novas formas de se fazer e de se pensar o turismo. O objetivo do presente estudo é caracterizar e analisar a experiência imersiva da Realidade Virtual proporcionada pelo uso do dispositivo Headset, na sua relação com o Turismo. Para tal consecução, tem-se por supostos: o mundo pós-moderno imprimiu novas formas de os sujeitos se relacionarem; as tecnologias são parte intrínseca dessas novas configurações e organizações, inclusive temporais e espaciais; os sujeitos estão sempre em deslocamentos (de diferentes naturezas); a realidade virtual é característica do mundo pós-moderno; a coexistência de diferentes abordagens conceituais de turismo e, as subjetividades presentes nas experiências turísticas. A metodologia utilizada tem caráter qualitativo, e, como tipo de pesquisa, busca-se a compreensão do problema de investigação a partir das teorias disponíveis, analisando-as e estabelecendo relações para explicitações sobre experiência turística imersiva que se dá no espaço virtual. Portanto, elementos que caracterizam natureza de pesquisa predominantemente bibliográfica. Para formação do marco teórico foram realizadas abordagens conceituais acerca do turismo, viagem, deslocamento, experiência turística, experiência imersiva, território, virtualização (virtual e virtualidade) e cibercultura para que se possa refletir e responder a questão: a experiência proveniente da imersão proporcionada pelo uso de headsets e de uma plataforma interativa multissensorial de Realidade Virtual, com conteúdo visual em 360°, pode ser considerada turística? Assim perspectivados, se o turismo for caracterizado como deslocamento físico, não se faz possível pressupor a existência de uma experiência turística virtual; porém, se a base teórico-analítica modificar-se, considerando turismo como um movimento para o desconhecido, há de se considerar a possibilidade de uma experiência com óculos 3D ser também caracterizada como turística. Nos desdobramentos ainda se fazem presentes muitos outros questionamentos, mas, a resposta ao questionamento inicial, se é ou não considerada experiência turística a realizada por meio de óculos 3D, dependerá das lentes analíticas sobre as quais o fenômeno está sendo investigado. Já há na literatura um aceno positivo para esse questionamento [resumo fornecido pelo autor].
Keywords: Turismo; Realidade Virtual; Tourism; Virtual Reality